Factors influencing Use of Human Resource Information System in Nepali Organizations (Journal of Business and Management Research, 2022)
Adoption of Human Resource Information System (HRIS) could be instrumental in gaining competitive advantage to organizations across all sectors. However, the adoption of HRIS is scanty in many organizations, especially in the developing countries. This study attempted to investigate application of Unified Technology Acceptance and Use of Technology (UTAUT) model in the context of adoption of Human Resource Information System (HRIS) in Nepali organizations. It also examined the mediating role of Behavioral Intention for actual use of HRIS. The study further investigated the moderating role of prior exposure for generating actual use of HRIS when behavioral intention already existed. One hundred thirty employees from the Human Resource Unit of different organizations participated in the study. The results showed that three factors - facilitating condition, performance expectancy, and hedonic motivation, generate behavioral intention for adoption of HRIS. The influence of these factors on actual use of HRIS was partially mediated by behavioral intention for adoption. Prior exposure of employees moderated the positive influence of three factors on actual use of HRIS. The implications of the study are discussed and limitations of the study are highlighted.